2009
DOI: 10.9775/kvfd.2011.4174
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye Faunası İçin Karacalarda İki Yeni Nematod Türü: Spiculopteragia spiculoptera (Guschanskaia, 1931) ve Küçük Varyetesi S. (Rinadia) mathevossiani (Ruchliadev, 1948)

Abstract: SummarySevere injury or dead six roe deer (Capreolus capreolus) which were brought to the clinics of the Faculty of Veterinary Medicine of Ondokuz Mayıs University by Provincial Directorate of Environment and Forest were examined for parasitological at 2007 to 2010. All roe deer were found infected with different gastro intestinal nematodes. Identified 17 nematode species are the first report in roe deer, and also Spiculopteragia spiculoptera and its dimorphic species S. (Rinadia) mathevossiani are the first r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In previous studies, carried out in Italy on roe deer, lower prevalences have been found (Poglayen et al, 1990;Poglayen et al, 1996). In Europe, on the other hand, equal prevalences have been found in Germany (Rehbein et al, 2000), Spain (Pato et al, 2013), Turkey (Umur et al, 2011), and slightly lower, again in Turkey (Bolukbas et al, 2012). Lower prevalences have been found in the Czech Republic (Vetyska, 1980), Austria (Schwarz et al, 2011), andPoland (Tomczuk et al, 2017;Balicka-Ramisz et al, 2003) Chabertia ovina showed the lowest prevalence in the large intestine 26.9 % (41.2 %) in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, carried out in Italy on roe deer, lower prevalences have been found (Poglayen et al, 1990;Poglayen et al, 1996). In Europe, on the other hand, equal prevalences have been found in Germany (Rehbein et al, 2000), Spain (Pato et al, 2013), Turkey (Umur et al, 2011), and slightly lower, again in Turkey (Bolukbas et al, 2012). Lower prevalences have been found in the Czech Republic (Vetyska, 1980), Austria (Schwarz et al, 2011), andPoland (Tomczuk et al, 2017;Balicka-Ramisz et al, 2003) Chabertia ovina showed the lowest prevalence in the large intestine 26.9 % (41.2 %) in the present study.…”
Section: Discussionmentioning
confidence: 99%